Large strain and high energy storage density in orthorhombic perovskite (Pb0.97La0.02)(Zr1−x−ySnxTiy)O3 antiferroelectric thin films - Mirshekarloo, Meysam Sharifzadeh (2013)
Antiferroelectric (Pb0.97La0.02)(Zr1−x−ySnxTiy)O3 (PLZST) thin films with orthorhombic perovskite structure were prepared on Si substrates by a chemical solution deposition process. A secondary pyrochlore phase, which was not detectable with x-ray diffraction, was revealed with transmission electron microscopy. The pyrochlore phase was effectively suppressed by the introduction of polyethylene glycol (PEG) in the precursor solution and applying PbO capping layer on the surface of the films. With the persistent and detrimental pyrochlore phase removed completely, our PLZST antiferroelectric thin films exhibited excellent electrical and electromechanical properties. A large energy storage density up to 13.7 J/cm3 was exhibited from the polarization measurement, and a strain of 0.49% under the clamping of the substrate was also achieved in the thin film with high Zr content.